Neem Essential Oil as an Antifungal Agent against Phyllosticta citricarpa - Joyce Maria Schuch; Carolina Rosai Mendes; Guilherme Lopes Cardoso; Carlos André da Veiga Lima Rosa Costamilan; Paulo Renato Matos Lopes; Renato Nallin Montagnolli; Guilherme Dilarri; Ederio Dino Bidoia (International Journal of Microbiology)
The fungus Phyllosticta citricarpa is a quarantine phytopathogen responsible for causing citrus black spot (CBS) disease. To export fruits to CBS-free countries, they must undergo a sanitation process to ensure disease control. In this study, neem essential oil (NEO) was tested against P. citricarpa for the first time as an alternative sanitizer. In vitro experiments were conducted to determine the inhibition concentration of NEO for P. citricarpa, and the mode of action of the essential oil was evaluated. In vivo assays were performed to simulate the sanitization process used in packinghouses. NEO was characterized by GC-MS/MS. The results revealed that NEO at 100 μL·mL−1 exhibited a similar inhibitory effect as copper oxychloride, suppressing 89.68 ± 1.14% of fungal mycelium growth. Fluorescence microscopy experiments demonstrated that NEO functions by disrupting the cytoplasmic membrane of fungal hyphae, leading to their death within 30 minutes of contact with NEO. GC-MS/MS characterization revealed a high presence of phenolic compounds, which serve as the primary antifungal agents responsible for the action against fungal hyphae. In vivo assays showed that NEO at 100 μL·mL−1 also reduced microorganisms (CFU mL−1) by 93.00 ± 3.88% compared to the negative control. Overall, the results demonstrate that NEO can effectively serve as an alternative sanitizer against P. citricarpa in citrus packinghouses. Our findings allow future studies to explore the use of NEO for sanitizing other fruits and combating different phytopathogens to broaden its potential application in fruit sanitation for export.